Effects of Gigantochloa apus String Bamboo Fiber Brushes on Heat-Cured Acrylic Resin Plate Surface Roughness - Azkya Patria Nawawi; Asih Rahaju; Annisha Putri Rivawati (International Journal of Dentistry)
Conclusion: Bamboo denture toothbrushes exhibit a lower abrasive effect than nylon denture toothbrushes, with the abrasiveness remaining below the threshold requirements established for dental materials.